Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Inovasi Produk Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan “Scarlett Whitening” - Julinha Betty Guterres Riu; IBN Udayana; Lusia Tria Hatmanti Hutami (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
The health of the skin and face is a matter of great concern to all women, because the skin and face are very visible parts of the body in terms of appearance so that the skin and face must be maintained and cared for. Therefore, the purpose of this study is to determine the effect of service quality, product quality, and product innovation on customer loyalty through customer satisfaction. This research is quantitative by taking 125 samples on consumers of Scarlett Whitening products in the city of Yogyakarta. Sampling was carried out using a non-probability method and the sampling technique was purposive sampling. Data was collected through sending a questionnaire link that was sent online to respondents. The data were analyzed using the IBM SPSS application. The results showed that the customer quality variable () had a significant positive effect on customer satisfaction (Z) with a value of < 0.001. Then the product quality variable () has no significant effect on customer satisfaction (Z) with a value of 0.103. Product innovation variable () has a positive and significant effect on customer satisfaction (Z) with a value of < 0.001. The customer satisfaction variable (Z) has a positive and significant effect on customer loyalty (Y) with a value of < 0.001. Furthermore, the service quality variable () has a positive and significant effect on customer loyalty (Y) with a value of 0.013. Product quality variable () has a positive and significant effect on customer loyalty (Y) with a value of < 0.001. Product quality variable () has a positive and significant effect on customer loyalty (Y) with a value of 0.002. In addition, the results of the study also show that customer satisfaction is able to act as an intervening variable for the effect of service quality, product quality and product innovation on customer loyalty for Scarlett Whitening products in the city of Yogyakarta. Keywords: Service Quality, Product Quality, Product Innovation, Customer Loyalty, Customer Satisfaction